On a Mechanical Interpretation of Self-energy in Electrostatics and Magnetostatics and an Interpretation of Faraday'\s Law - Chankit Khanchong (Science Faculty of Chiang Mai University, 2019)
We use a consistency argument from a mechanical perspective to interpret the existence of electrostatic and magnetostatic self-energy. According to the magnetostatic self-energy introduced beforehand in this mechanical context, we can use the energy-conservation statement at the outset to interpret Faraday’s law. This approach to Faraday’s law reverses the typical arguments found in standard texts.